Multivariate Filter Estimation of Potential Output for the Euro Area and the United States - Alichi, Ali (IMF Working Papers; Working Paper ;, 2015)
The estimates of potential output and the output gap presented in this paper are not official IMF estimates. The programs and potential output estimates in this paper can be downloaded from www.douglaslaxton.org.The views expressed in this paper are those of the authors and do not necessarily represent those of the IMF or IMF policy. The authors would like to thank the European Department of the IMF for helpful comments. All errors and omissions are our own.